Improved hydrocarbon reservoir detection using enhanced transmitter - Rauf, M. (Institute of Electrical and Electronics Engineers Inc., 2017)
Marine Control Source Electromagnetic (MCSEM) method is recently considered as the de-risking tool for the hydrocarbon exploration in offshore environment. The method conventionally uses Horizontal Electric Dipole (HED antenna, towed by a ship that transmits low-frequency waves. The received signal describes the resistivity contrast hence, the oil presence information is revealed. Towing the transmitter accurately, and increasing current amplitude to increase the magnitude of received signal for better prediction of the oil is yet a challenge for the industry. In this research work, the enhanced detection of the oil reservoir by using the toroidal magnetic feeders over the conventional HED is presented. The addition of the magnetic feeders as the field magnifiers shows the considerable increment in the magnetite of the received signal. Whereas the improved oil delineation capability was achieved by stirring the waves towards the oil layer by dis-balancing the transmitted signal using magnetic feeder. The promising results by the designed and simulated enhanced transmitter provided 42 oil delineation as compared to the 34 by the conventional straight HED. This work opens the new door in the field of stirring the low-frequency EM waves towards the target for the confident prediction. © 2016 IEEE.